Membangun Kepercayaan Diri Peserta Didik Melalui Pendidikan Gerak: Perspektif Intervensi Keterampilan Motorik - Muh Ilham Aksir; Andi Atssam Mappanyukki (Journal Physical Health Recreation (JPHR), 2024)
Student Self-Confidence Through movement education is very important in helping to overcome fear and doubt. Through movement education programs can build student self-confidence. The study used a quantitative approach with an experimental design. The sample consisted of 100 students from elementary schools in Makassar City in the 2023/2024 academic year. The experimental group followed a program that included physical activities of coordination, balance, and strength. Meanwhile, the control group did not receive intervention during the same period. Before and after the intervention, participants underwent a self-confidence test using a valid and reliable measuring instrument, the Children's Self-Perception Scale, interviews were also conducted with several participants. The results of the t-test showed a significant difference between the two groups, the average level of self-confidence of the experimental group was 2,320 points higher than the control group, with a difference within the 95% confidence interval between 1,927 and 2,713. Implementing a structured program, educators can help students build stronger self-confidence so that it has a positive impact on other aspects. Further research is needed to explore other factors that may influence the relationship between movement education and self-confidence, and to develop more effective interventions in the future.